Total and high-molecular-weight adiponectin levels and prediction of insulin resistance - Horakova, Dagmar; Stepanek, Ladislav; Nagelova, Radka; Pastucha, Dalibor; Azeem, Katerina; Kollarova, Helena (Endokrynologia Polska, 2018)
INTRODUCTION: Adiponectin is a peptide secreted by adipocytes; its reduction is associated with obesity-related disorders, including insulin resistance (IR). The study analysed levels of total adiponectin and its high-molecular-weight (HMW) oligomer in a group of metabolically healthy adults and in patients with type 2 diabetes mellitus (T2DM) to evaluate these levels as potential predictors of the presence of IR. MATERIALS AND METHODS: The study comprised 269 metabolically healthy adults and 300 patients with T2DM. Anthropometric and bio-chemical indices were measured, including total and HMW adiponectin levels; the Homeostatic Model Assessment of IR (HOMA-IR) index was calculated, and logistic regression analysis was used to predict the presence of IR. RESULTS: In healthy individuals, both total and HMW adiponectin levels were significantly higher than in diabetic patients. Total and HMW adiponectin levels were moderately correlated with the HOMA-IR index. Logistic regression analysis showed that increased levels of both total adiponectin (odds ratio [OR] 0.598, 95% confidence interval [CI] 0.483-0.723) and the HMW form (OR 0.360, 95% CI 0.242-0.511) are protective factors for the development of IR. The cut-off levels were 4.22 mg/L for total adiponectin and 2.75 mg/L for HMW adiponectin. The results are valid for middle-aged European adults. CONCLUSIONS: Adiponectin levels below the indicated cut-offs may predict a potential risk for the development of IR.
Keywords: Female; adiponektin; ženské pohlaví; Diabetes Mellitus, Type 2; Adiponectin; lidé; diabetes mellitus 2. typu; prognóza; Risk Factors; molekulová hmotnost; Male; Aged; Insulin Resistance; inzulinová rezistence; rizikové faktory; Prognosis; lidé středního věku; senioři; mužské pohlaví; Molecular Weight; Middle Aged; Humans